Neo-tributary geopolitics in transnational higher education (TNHE): a regional analysis of Sino-foreign higher education partnerships. (15th March 2023) - Si, Huili; Lim, Miguel Antonio
ABSTRACT : This research explores how geopolitics and 'Neo-tributary' relations influence the distribution of TNHE partnerships in China. Specifically, this research situates China's TNHE cooperation in policy reforms and designs since 2010, and explores how geopolitics influences the regional practice of re-organisation of the joint programmes between 2018 and 2020. The findings show that, on one hand, China's central government prioritises the TNHE partnerships in China's local regions: East China, Central China and West China; and on the other hand, alongside the traditional partner countries, such as the UK and the US, the emerging BRI region enjoys more new Sino-foreign HE partnerships than other foreign partners. This research develops the discussion based on the categories of trade and diplomacy linkages; cultural assimilation; and image building (Pan, Su-Yan, and Joe Tin-Yau Lo. 2017. "Re-Conceptualizing China's Rise as a Global Power: A Neo-Tributary Perspective." The Pacific Review 30 (1): 1–25.), and concludes with some of the implications of these trends on the 'new' geopolitics of knowledge in a Neo-tributary system.